2015
DOI: 10.1039/c5cc03434e
|View full text |Cite|
|
Sign up to set email alerts
|

Combination of inverse electron-demand Diels–Alder reaction with highly efficient oxime ligation expands the toolbox of site-selective peptide conjugations

Abstract: A modular approach combining inverse electron-demand Diels-Alder coupling (DARinv) and oxime ligation expands the toolbox of bioorthogonal peptide chemistry. Applicability of versatile site-specific bifunctional building blocks is demonstrated by generation of defined conjugates comprising linear, cystine-bridged and multi-disulfide functional peptides as well as their conjugation with hybrid silsesquioxane nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Another approach exploited the oxime ligation to modify peptides, that contain a glyoxylyl group, with aminooxy‐bearing tetrazines (Figure D; 1) and dienophiles. The results showed that both click reactions, the IEDDA reaction and the oxime ligation, are orthogonal to each other . Tetrazines were also coupled to peptides in solution by EDC coupling, thiol‐Michael addition (Figure D; 2) or generating a thiourea bond (Figure 2D; 3) .…”
Section: Iedda Reactions In Peptide Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach exploited the oxime ligation to modify peptides, that contain a glyoxylyl group, with aminooxy‐bearing tetrazines (Figure D; 1) and dienophiles. The results showed that both click reactions, the IEDDA reaction and the oxime ligation, are orthogonal to each other . Tetrazines were also coupled to peptides in solution by EDC coupling, thiol‐Michael addition (Figure D; 2) or generating a thiourea bond (Figure 2D; 3) .…”
Section: Iedda Reactions In Peptide Chemistrymentioning
confidence: 99%
“…After modification of the peptides and their respective counterpart with a diene and dienophile, the IEDDA reaction can be performed on solid phase or in solution. Mostly, peptides have been modified by the IEDDA reaction in solution using different solvents such as water, and aqueous solutions of DMSO, ethanol, acetonitrile, or chloroform . Adding a lipophilic solubilizing agent is often indispensable because of high hydrophobicity of the tetrazine.…”
Section: Iedda Reactions In Peptide Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…A typical DA reaction is reversible, for example through the application of heat energy. The Diels-Alder mechanism with inverse electron demand (IEDDA), in contrast, is an irreversible cycloaddition between an electron-rich dienophile and an electron-poor diene, e.g., tetrazines, that was found to be a valuable tool for effective bioorthogonal conjugations [ 65 , 66 , 67 ]. Macromers that combined thermogelling properties and functional groups for cross-linking by a DA mechanism are poly( N , N -dimethylacrylamide- co -furfuryl methacrylate) and poly(NiPAAm- co -furfuryl methacrylate) [ 68 , 69 ].…”
Section: Macromers With At Least Two Types Of Functional Groups Fomentioning
confidence: 99%
“…719 In recent years, cyclopropene, a less bulky strained alkene, has also been successfully applied as a robust bioorthogonal probe. 2327 Curiously, cyclobutenes, a class of small and strained alkenes known to be reactive towards IEDDA reactions, 28–30 have received much less attention, with most efforts involving derivatives of the Reppe anhydride, a bicyclic derivative of cyclooctatetraene. 31 Monocyclic cyclobutenes, such as those discussed here, have surprisingly good thermal stability, 29–30 and, in contrast to cyclopropenes, 25 have good chemical stability even in the absence of additional substituents on the alkene.…”
mentioning
confidence: 99%